Design and Application of PIs in Indonesian He: Key Policy Implications - Simanjuntak, Risa R. (Humaniora, 2011)
This literary studies focuses in discussing key political implications in the design and application of Performance Indicaators (PIs) in Indonesia include competition and government’s agenda on research in HE. It is found that the competition is mainly addressed by the current practice of Journal Accreditation as giving benchmark for quality in research. This government’s agenda on research has caused some dilemmas in managing education as complex process. Some suggestions are given in answering to these dilemmas. First, PIs should be regarded as products of current situations and demands. Second, application of the design will have to be assisted by the nature of the institution. PIs should also not be considered as absolute indicators for quality but rather as catalyst toward development.